PARENTAL INVOLVEMENT IN BUDDHIST STUDENT LEARNING IN THE NEW NORMAL ERA - Wulandari, Dippa; Parsiyono, Parsiyono; Dewi, Sukhitta (Jurnal Pencerahan, 2023)
The purpose of this study was to describe the involvement of parents in the learning of Buddhist students in the new normal era, to describe the learning model applied by parents, and to describe the appropriate learning model to be applied by parents. The method used in this research is descriptive qualitative. The subjects in this study consisted of parents, Buddhist students, and teachers at SD Negeri Wates 01. The data collection techniques used by the researcher were interview, observation, and documentation tecniques according to the three instruments. Ways to ensure the validity of the data obtained were through continuous observation, triangulation, member check, credibility, transferability, dependability, and confirmability. The researcher analyzed the data obtained using the Miled & Huberman method. The results of this study include forms of parental involvement, namely accompanying children to study and checking the tasks that have been carried out during tutoring, paying attention and helping children while studying, asking children’s assignments, supervising and reminding children to learn. Meanwhile, the learning model applied by parents is the direct learning model, the questioning learning model, the inquiry learning model, and the discovery learning model. The appropriate learning model to be applied to parents is the learning model which has been applied plus the development of the nature of Mettā dan Karuņā so that the children’s learning process can be carried out in accordance with the Buddha’s teachings.